The use of modern geoinformation technologies in the formation of electronic maps - Khаkimovа Kаmolа Rаkhimjonovnа; Khusanova Mashkhura Islamovna (Zien Journals, 2024)
This article provides information on the use of modern geo-information technologies in creating electronic maps, the advantages of creating electronic digital maps, and cartographic sources
Keywords: Map; GIS; Global Mapper; ArcGIS